Non-covalent functionalization of graphene sheets by pyrene-endcapped tetraphenylethene: Enhanced aggregation-induced emission effect and application in explosive detection - Zhang, Yumin; Li, Huanran; Wu, Qing-Yun; Gu, Lin (Frontiers in Chemistry, 2022)
In this work, a dispersible graphene based material with a characteristic of aggregation induced emission (AIE) was prepared by wet chemical reduction of graphene oxide (GO). During the GO reduction process, a conjugated molecule TPEP containing tetraphenylethylene (TPE) and pyrene was employed as a stabilizer because of the π-π interactions and the wrapping effect. The as-prepared rGO-TPEP not only has good dispersion in solution, but also processes the AIE feature. Its fluorescence intensity is 2.23 times higher than that of TPEP at the same condition. The unique optical properties and AIE effect enable the rGO-TPEP as a chemical sensor for highly sensitive explosive detection in aggregated state and solid state. In the aggregated state, trace 2,4-dinitrotoluene (DNT) can be detected by the rGO-TPEP even when the concentration is as low as 0.91ppm, and the quenching constant is as high as 2.47×104 M-1.